Evaluation of First Line Agents’ Resistance Amongst Campylobacter Isolates Using MIC Breakpoints at Aga Khan University Clinical Laboratory - Iftikhar, Irim; Irfan, Seema (Infectious Diseases Journal of Pakistan, 2023)
Background: Campylobacter is one of the most common causes of gastroenteritis especially in Pakistan, with an increasing drug resistance. Usually erythromycin and ciprofloxacin are considered the first line agents however, over a period of time, resistance against these antimicrobials has been observed in various regions of the world. Growing erythromycin resistance is of concern since these strains mostly turn out to be multidrug resistant and there are very few options available to fight against them. The aim of the study is to evaluate frequency of erythromycin and ciprofloxacin resistance in Campylobacter species. Material and Methods: A total of 107 isolates were isolated from stool as well as blood samples from Jan 2014 to March 2016 and identified by conventional tests. Minimum inhibitory concentration (MIC) of erythromycin and ciprofloxacin was performed by using agar dilution method on 5% defibrinated sheep blood Mueller-Hinton agar plates as per CLSI recommendation. C. jejuni ATCC® 33560 is used as control for agar dilution testing. Results: A total of 107 isolates were collected over the period of 2014 to 2016. Out of 107, 14.02% of the isolates were from blood samples while 885.98% were collected from stool. Seventy seven (77%) were C. jejuni while the rest were labeled as Campylobacter spp. Erythromycin resistance was 14%, ciprofloxacin resistance 93%. Of the 15 erythromycin strains, 11 were C. jejuni while 4 were Campylobacter spp. All 15 erythromycin resistant isolates were 100% resistance to ciprofloxacin. Conclusion: There has been significant rise in resistance to first line agents in Campylobacter resulting in difficulty in identifying the better treatment option for Campylobacter and demanding the newer treatment options. Key words: Campylobacter species, erythromycin, ciprofloxacin resistance